Analisis Pengaruh Tata Guna Lahan terhadap Efektivitas Daerah Irigasi Cipalebuh - Agun Gunawar; Sulwan Permana (Jurnal Konstruksi, 2023)
Cipaleubuh Irrigation gets water from the Cipaleubuh River for the needs of rice fields and plantations in Pameungpeuk. To determine water availability and effectiveness of irrigation channels. This research was conducted to determine the Cipaleubuh Bend River Discharge and Irrigation Discharge by taking into account current conditions. The research location is Cipaleubuh Dam to Cipaleubuh Irrigation with an area of ”‹”‹1016 ha. The largest river discharge is 5.66 m3/second using the FJ Mock Method, evapotranspiration calculations using 10 years of climatology data and 10 years of rainfall data using the Penman Monteith Method. The Cipalebuh irrigation area with an area of ”‹”‹1,016 hectares requires water withdrawals, water availability is still sufficient from January to June, and scarce from July to October, but water availability is low at the end of the year. reduced capacity. Enough for November and December. Based on the analysis results, the maximum river discharge was 5.66 m3/s in March. A water intake of 1.65 l/sec/ha at the key requires a required water volume of 1016x1.65 = 1676.4 l/sec. Cipaleubuh land use is divided into river areas, plantation areas, gardens, irrigated rice fields, bushes and agricultural land. Fertile land contributes 30.880% compared to 2.017% for river water. However, water needs can be met with DI. Effective Cipaleubuh.